2022
DOI: 10.3390/nu14071451
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Levels of the Perinatal Period Shape Offspring’s Weight Trajectories through the First Year of Age

Abstract: Background: Leptin is a hormone regulating lifetime energy homeostasis and metabolism and its concentration is important starting from prenatal life. We aimed to investigate the association of perinatal leptin concentrations with growth trajectories during the first year of life. Methods: Prospective, longitudinal study, measuring leptin concentration in maternal plasma before delivery, cord blood (CB), and mature breast milk and correlating their impact on neonate’s bodyweight from birth to 1 year of age, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Contradictory to the above data, there are studies that have demonstrated lower maternal serum leptin levels between growth-restricted cases and uncomplicated controls. However, the findings of the current published bibliography alongside the results of our meta-analysis suggest that leptin may indeed have a role in the pathophysiology of several adverse events of the pregnancy, and it has been proposed that the comparison of leptin concentrations against the reference values that have been published [ 36 ] might be a useful prediction asset of such complications [ 14 ]. The studies conclude that both the up- and down-regulation of serum leptin is originating from the deterioration of the placenta, with a number of published data revealing the critical effect of those alterations in preterm newborns without being limited in the antenatal period but also influencing the growth trajectories of the affected neonates [ 14 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Contradictory to the above data, there are studies that have demonstrated lower maternal serum leptin levels between growth-restricted cases and uncomplicated controls. However, the findings of the current published bibliography alongside the results of our meta-analysis suggest that leptin may indeed have a role in the pathophysiology of several adverse events of the pregnancy, and it has been proposed that the comparison of leptin concentrations against the reference values that have been published [ 36 ] might be a useful prediction asset of such complications [ 14 ]. The studies conclude that both the up- and down-regulation of serum leptin is originating from the deterioration of the placenta, with a number of published data revealing the critical effect of those alterations in preterm newborns without being limited in the antenatal period but also influencing the growth trajectories of the affected neonates [ 14 ].…”
Section: Discussionmentioning
confidence: 96%
“…The studies published so far have demonstrated both higher [ 9 , 10 , 11 ] and lower [ 12 , 13 ] levels, as well as no association [ 14 , 15 ] between maternal serum leptin levels and fetal growth restriction. Most of the available data suggest that the mean levels of leptin appear to be elevated in growth-restricted fetuses compared to appropriately grown controls, a difference that becomes further aggregated when growth restriction is accompanied by the development of preeclampsia [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the reported relationships among the analyzed parameters, including perinatal risk factors, in mother-infant dyads are also summarized (Table 2). Only seven reports presented data for three different biological materials, namely for maternal plasma, cord plasma, and placenta [113,127,128,143,146,148,156], and two papers analyzed three different biological materials in another layout, namely for maternal plasma, cord plasma and maternal milk, or infant's plasma [119,144]. However, the most frequently studied pair of biological materials in the analyzed set of studies was that of maternal plasma and cord serum (23 out of 47), followed by maternal plasma and breast milk (8 out of 47) (Table 2).…”
Section: Adipokines In Maternal-infant Dyadmentioning
confidence: 99%